Perrine's story and structure - Greg Johnson; Arp, Thomas R.; Johnson, Greg, 1953- (Boston, MA : Wadsworth/Cengage Learning, 2012)
"More than fifty years ago, Laurence Perrine pioneered an engaging approach to teaching literature ... Since then, millions of students have used Perrine's introductions to plot, character, theme, and other elements of fiction, gaining an understanding of fiction and developing essential skills in critical reading, analysis, and writing"--P. [4] of cover.
Includes bibliographical references and index
Keywords: Short story; Short stories